Differences in Oxygen Saturation before and after Physical Activity in Exercise Trained Men and Untrained - Huldani, Asnawati, Dona Marisa, Wafa Ahdiya, Muhammad Hasan Ridhoni, Annisa Putri Febriyanti, Raida Namira, Rizky Nabila Febriani (Drugs and Cell Therapies in Hematology, 2022)
Oxygen saturation is the amount of oxygen transport capacity in the blood expressed in percent with normal values ​​ranging from 95-100%. The need for oxygen will increase during physical exercise, so that ventilation and blood flow will increase which causes more oxygen to diffuses into the pulmonary capillaries and binds to hemoglobin. Writing this literature review is to analyze the difference in oxygen saturation before and after physical activity in men who exercise and don’t. The reference data in this article study was obtained by searching using PubMed and Google Scholar published in 2012 to 2021. After the search and article selection process, 8 articles were included in this literature review. A total of 3 articles showed that there was an increase in oxygen saturation after physical activity in both people who did sports and those who did not. Meanwhile, the other 5 articles showed that there was a decrease in oxygen saturation after physical activity in both people who exercised and those who did not. It can be said that oxygen saturation after doing physical activity, both people and not will experience a decrease. The decrease was greater in people who did no more than people who exercised.